EU Clean Energy Transition and Challenges for International Investors: Comparative Review of German Practice - A. V. Zimakov; E. V. Popov (Sravnitelʹnai͡a︡ politika (Moscow, Russia), 2022)
Clean energy transition in the EU opens up wide investment opportunities for innovative international entrepreneurship. However, the non-linearity of the energy transition, as well as the multi-level and complex nature of the transformation process, implies tackling economic and legal challenges. To examine such challenges in detail, an analysis of three international investment arbitration cases that were brought in for resolution by transnational energy companies against the European Union is carried out using the comparative methodology and taking the example of Germany as the leader of the EU energy transition. Having done the comparative review, the conclusion is drawn that rapid changes in legislation due to the logic of the energy transition process may lead to violation of the legitimate expectations of investors in ensuring a stable and predictable legal regime. Thus, the credibility of the EU states to provide a predictable and stable legal regime for international investors is under scrutiny.